Terapia ocupacional e a questão social no Brasil : uma análise de suas publicações - Duarte, Maria Luiza Mangino Cardoso (Universidade Federal de São Carlos, 2016)
In Brazil, where social issues arising from the structural inequality of a capitalist society did not lead to configuring a State of Social Welfare at any time in its history and that, moreover, it coexists with extreme levels of wealth concentration, encouraged the question about how, nowadays, this social issue is whether or not considered by occupational therapists. Understanding that occupational therapy is a profession that can direct its interest of study and involvement to the social inequalities and its problematics, and highlighting interventions and therapeutic-occupational propositions that occur with individuals who are on the margins of the social organization, this project made a proposal of research that goes back to the relationship between occupational therapy and the "social issues" in Brazil, focusing on the publications produced by researchers until March 2015, when data collection ended. The survey was conducted from the CNPq Research Groups Directory in the Lattes Platform, where occupational therapists researchers working in the occupational therapy subarea were selected in this directory. Then an assessment was held in their resumes on the same platform in order to gather all its productions in format of articles, books and / or book chapters, so that later those related to the subject studied could be selected. In addition to this source of information, all publications in this area in the two indexed Brazilian journals in the field were gathered. The aim was to bring together the production of researchers in occupational therapy with what has been brought in knowledge dissemination vehicles in the area. The data collected after the application of the inclusion criteria for the study were gathered in 112 texts of 155 different authors. The content thereof permitted to categorize and analyze what was produced in the academic area, allowing the apprehension of the theoretical foundation of the relationship between occupational therapy and social issues in Brazil. It is noteworthy that the productions on the theme intensified from the 2000s, and mostly cover the adult population. What has been proposed by social occupational therapy in Brazil and the authors linked to METUIA Project marks sharply the set of this production. Moreover, it is clear that professionals turn to the demands arising from the social question in Brazil, noting that occupational therapy has indeed tools and resources to do so.
Keywords: Terapia ocupacional; Tendências; Questão social; Terapia ocupacional social; Occupational Therapy; Trends; Social Issues; Social Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL